Synthesis of the anti-oxidant eugenol benzoate using Candida rugosa lipase immobilized onto multi walled carbon nanotubes - Abdullah Ismail, Shawnm (2014)
Multi walled carbon nanotube (MWCNTs) having high surface area was used for the immobilization of lipase from Candida rugosa (CRL) by physical adsorption. The ability of the MWCNT immobilized CRL was compared against the free CRL in the esterification of benzoic acid with eugenol to produce the antioxidant eugenol benzoate, a potent lipoxygenase inhibitor. In this study, the effect of four parameters; reaction time, temperature, molecular sieves and enzyme loading were evaluated. The maximum yield of ester of reactions catalyzed by immobilized CRL and free lipase were found to be 31.62 and 27.2%, respectively. The study revealed that the optimal conditions for the highest yield of ester attained for both free CRL and immobilized CRL were similar. The attained optimum conditions were 5 mg/mL enzyme, 0.5:1.5 molar ratio of benzoic acid/eugenol dissolved in 38.5 mL chloroform, 500 mg of molecular sieves with 50 mL total volume of reaction mixture, stirred under 200 rpm at 40oC for 4 h. It was observed the MWCNT immobilized CRL afforded slightly higher yield of ester in all parameters investigated as compared to the free CRL. The outcome suggests that the MWCNT immobilized CRL could be used to synthesize eugenol benzoate. Furthermore, treatment of the esterification process is now easier due to simpler methods of separation of the end product and the biocatalyst could be recycled.